Large-Scale Graphene Production Techniques for Practical Applications - 배수강; 이승기; 박민 (한국진공학회, 2018)
Many studies have been conducted on large-scale graphene synthesis by chemical vapor deposition. Furthermore, numerous researchers have attempted to develop processes that can continuously fabricate uniform and high-quality graphene. To compete with other types of carbon materials (carbon black, carbon fiber, carbon nanotubes, and so on), various factors, such as price, mass manufacturing capability, and quality, are crucial. Thus, in this study, we examine various large-scale graphene production methods focusing on cost competitiveness and productivity improvements for applications in various fields.